Constraints and Opportunities in Low- and Middle-Income Countries: Essays on Youth Fertility, Technology Adoption, and Credit Access - Donoso-Pena, Leticia (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Economics.; Advisor: Jenny Aker.; Committee: Eoin McGuirk, and Margaret McMillan.; Keyword: Economics.